Management and utilization of seals in Greenland. Revised April 2012. - Unkn Unknown (Government of Greenland, Department of Fisheries, Hunting & Agriculture, 2012)
1. Species: There are six different species of seals in the Greenlandic waters. Five of the species have been hunted for centuries, but today the catch is focused on the harp seal, ringed seal and hooded seal with great importance to the Inuit hunters. The seal populations hunted in Greenland's waters counts more than 12 million seals. 2. Sustainability and biological advice: There are no quotas on seals in Greenland, as the harvest level is relatively low compared with the number of seals. The populations of harp and hooded seals have, however, also been subjected to commercial sealing by Canadian, Norwegian and Russian sealers, and their numbers and reproduction have, therefore, been monitored carefully for many decades. These species are now managed after an internationally-recognized, conservative cautionary approach within marine mammal management called Potential Biological Removal (PBR). According to the Red List of Greenland (2007) none of the three species are endangered. The Red List's assessments are carried out by the guidelines of the international Red List; conducted by The International Union for Conservation of Nature (IUCN). Furthermore, in 2004, IUCN openly supported sustainable harvesting principles in relation to the abundant seal populations; rather than protection of these species. - Harp seal: Harp seals are divided into three populations; one that breeds in the White Sea (Russia), one in the Greenland Sea (off Northeast Greenland) and one off Newfoundland (Canada). Most Greenland catches are from the population shared with Canada. The latest survey result for this population is from 2008, which found that 1.6 million newborn pups were born that spring, and that this corresponds to a total population of about 8 million. The population is believed to have increased further, so that it now counts more than 9 million seals. The current population might be at its highest level ever; hence, higher than before the commercial hunt began. This is possible because other components in the ecosystem, ex. cod and some of the large whales, are relatively smaller compared to what they have been. The total allowable catch (TAC) for Canada was set to 400,000 in 2011, but only 38,018 harp seals were taken. The Greenland catches has in the latest decade averaged 82,000/yr. harp seals. - Ringed seal: The world population of ringed seals is estimated to be around 5-7 million seals. Approximately 50 % of the Greenland catch of about 78,000/yr. since 2000, is taken in Baffin Bay. The population of ringed seals in Baffin Bay and adjacent areas is estimated to be around 1.2 million seals (NAMMCO). Sustainability of the catch is assumed, because the ringed seal is widely and evenly distributed across most of the Arctic. They do not concentrate in breeding areas like the harp seals, and can, therefore, not be hunted in the same industrial way. The area, where they are hunted by the Inuit in Greenland and Canada, only constitute a tiny fraction of their habitat. 2 Hooded seal: Close to all catches of hooded seals in Greenland, average of 4,600/yr., since 2000, is from the Northwest Atlantic population, which is estimated to be around 600,000 seals (ICES/NAFO). The Canadian TAC, which takes a free hunt in Greenland into account, is set to 8,200, but less than 100 has been taken in recent years. 3. Hunting methods in Greenland: The catch of harp seals takes place all year round, but predominantly during summer and falls in open water and is a small-scale hunt. The hunter localizes the seal and shoots it with a rifle. In northern Greenland during the dark winter months netting is the prevailing method for the hunters to catch ringed seals. In spring, when ringed seals haul-out on the ice, hunters use white screens to sneak up to an appropriate shooting distance and shoot the seal dead in the head. In The European Food & Safety Agency’s (EFSA) study, the rifle hunt is accepted as a humane hunting method. 4. The Greenlandic catch: There are about 2,100 full time and 5,500 leisure time hunters in Greenland. Altogether, there are just under 8,000 hunters in Greenland. The full time hunters constitute almost 7 % of the work force (app. 32,000) in Greenland (2011). 5. Economy – household as well as national: For the 2,100 professional hunters in Greenland, the income from the seal hunt is vital. The household economy for the hunter is mixed. The income from the seal hunt (from selling and/or giving the meat) serves as a subsistence supplement to the barter economy still existing in small communities dispersed in Greenland. It also serves as direct cash flow income for the hunter; namely the sale of the seal skin from which some hunters get approx. half of their cash income covered, in order to feed their families. Often, the hunter in smaller communities is the breadwinner of the family. The average income for a hunter’s municipality (e.g. Qaanaaq in northern Greenland) is approx. 16,000 € (2010). In terms of the national economy, the seal skin export has been steadily decreasing over the last couple of decades. It used to constitute an export item, besides the dominant export of fishery products, which account for 93 % (2011). An export hindrance would create social pressure on the national economy as hunters, relying on the cash flow income, would turn to social security benefits from the Greenlandic authorities. Furthermore, the seal skin processing has an intra-economic value, as different seal products are sold as handicrafts, clothing, national garments etc., some of which is sold to tourists. 6. Culture and tradition: Seal hunting is an important part of the Inuit culture, tradition and identity in Greenland. Since the arrival of the first Inuit, seals have provided basic nutrition as food for humans and dogs. Furthermore, items (blubber and skin) have provided shelter, fuel, lightning, tools, covers for tents and kayaks, as well as, clothing. The seal also plays an immense role in Greenlandic mythology. Today, the Inuit in Greenland have access to the items of the modern world, but the seal is still hunted for food and clothing, and as part of a traditional legitimate leisure activity, in which all parts of the seal are used or consumed. 3 7. Rights of Indigenous Peoples: The Inuit in- and government of Greenland call upon the declaration of the rights of Indigenous Peoples, which all EU Member States have signed. Relevant articles related to the hindrance of commercial seal hunting are: - Indigenous Peoples have the right to freely pursue their economic […] development (art. 3) - Indigenous Peoples have the right to not be subjected to forced assimilation or destruction of their culture (art. 8). - Indigenous Peoples have the right to be secure on the enjoyment of their own means of subsistence […] and to engage freely in […] economic activities (art. 20). - States shall consult […] in good faith with the Indigenous Peoples concerned […] in order to obtain the free and informed consent prior to the approval of any project affecting their […] resources (art. 32, §2). 8. Legislation - regulation, control and monitoring: In Greenland, the law on hunting from 1999 and the law on protection of nature and wildlife from 2003 constitute the overall frame regarding wildlife regulation. From December 1st, 2010, a national executive order regarding the protection of seals and regulation of sealing came into force. The municipalities (four) set local regulation on seal hunting; but, as a rule of thumb, seals can be hunted all year around; provided that hunters have a permit. There are no quotas on the seals hunted; however, the permits are used to control and monitor the harvest, as hunters are required to report their annual catches. 9. International cooperation on seals: Greenland cooperates with the International Council for the Exploration of the Sea’s (ICES/NAFO) Working Group on Harp and Hooded Seals and, also, with the North Atlantic Marine Mammal Commission (NAMMCO), which has a task force covering the studies and monitoring of seal populations. Within NAMMCO, a Seal Management Committee has been established in 2006; chaired by Greenland. 10. International trade bans on seal skins and seal products: The Marine Mammal Protection Act (MMPA) of the United States enacted on October 21, 1972. The Council Directive 83/129/EEC (European Economic Community) of 28 March 1983 concerning the importation into Member States of skins of certain seal pups and products derived therefrom. Regulation (EC) No 1007/2009 of the European Parliament and of the Council of 16 September 2009 on trade in seal products, including an exemption for Inuit. Commission Regulation (EU) No 737/2010 of 10 August 2010 laying down detailed rules for the implementation of regulation No 1007/2009.